2011
DOI: 10.1177/1933719110374115
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of MicroRNAs and mRNAs in Human Placentas From Pregnancies Complicated by Preeclampsia and Preterm Labor

Abstract: MicroRNAs (miRNAs) have emerged as key regulators of gene expression stability implicated in cell proliferation, apoptosis, and development, whereas their altered expression has been associated with various pathological disorders. The objective of this study was to assess the expression profile of miRNAs and their predicted target genes in placentas from patients with preeclampsia (PC) and preterm (PT) labor as compared to normal term (NT) pregnancies. Using microarray profiling of 820 miRNAs and 18,630 mRNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(205 citation statements)
references
References 72 publications
(124 reference statements)
7
191
2
5
Order By: Relevance
“…Hu et al (2009) performed a highthroughput miRNA microarray study and revealed significantly increased levels of 7 miRNAs (miR-16, miR-29b, miR-195, miR-26b, miR-181a, miR-335, and miR-222) in placentas derived from pregnancies with severe PE, occurring after 34 weeks, compared with those derived from healthy controls. (Zhu et al, 2009;Enquobahrie et al, 2011;Mayor-Lynn et al, 2011;Zhang et al, 2011). Enquobahrie et al (2011) further confirmed the downregulation of previously identified miRNA candidates (miR-1, miR-328, miR-139-5p, miR-500, and miR-1247) and found two novel miRNA candidates to be downregulated in pregnancies complicated by PE (miR-584 and miR-34c-5p).…”
Section: Differential Expression Of Mirnas Between Pre-eclamptic Andsupporting
confidence: 65%
“…Hu et al (2009) performed a highthroughput miRNA microarray study and revealed significantly increased levels of 7 miRNAs (miR-16, miR-29b, miR-195, miR-26b, miR-181a, miR-335, and miR-222) in placentas derived from pregnancies with severe PE, occurring after 34 weeks, compared with those derived from healthy controls. (Zhu et al, 2009;Enquobahrie et al, 2011;Mayor-Lynn et al, 2011;Zhang et al, 2011). Enquobahrie et al (2011) further confirmed the downregulation of previously identified miRNA candidates (miR-1, miR-328, miR-139-5p, miR-500, and miR-1247) and found two novel miRNA candidates to be downregulated in pregnancies complicated by PE (miR-584 and miR-34c-5p).…”
Section: Differential Expression Of Mirnas Between Pre-eclamptic Andsupporting
confidence: 65%
“…We previously reported that miR-181a expression was significantly increased in placental samples from women with severe PE [18]. This result was confirmed in two subsequent reports [19,20]. miR-181a is strongly expressed in bone marrow (BM) and thymus, can modulate hematopoietic lineage differentiation, and has an important role during T-and B-cell development [21][22][23].…”
Section: Introductionsupporting
confidence: 67%
“…One specific microRNA found in all three studies is miR-210 (Mayor-Lynn et al, 2011;Pineles et al, 2007;Zhu et al, 2009). In two studies, miR-210 was found to be increased by a three-fold in (severe) pre-eclampsia, while Lynn and coworkers found a small downregulation.…”
Section: The Involvement Of Micrornas In Preeclampsiamentioning
confidence: 98%
“…Several studies aimed to identify miRNAs involved in pre-eclampsia by comparing miRNA expression between normal and pre-eclamptic placentas (Mayor-Lynn et al, 2011;Pineles et al, 2007;Zhu et al, 2009). Each study found various miRNAs that were either up-or downregulated in pre-eclamptic placentas.…”
Section: The Involvement Of Micrornas In Preeclampsiamentioning
confidence: 99%